PERAN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP PENGEMBANGAN INNOVASI DAN BUDAYA KERJA DALAM ORGANISASI PENDIDIKAN - Mahayana, Dewa Komang Tri; Hidayat, Dylmoon (STKIP Pesisir Selatan, 2022)
Developing a quality culture in educational institutions can be achieved by developing educational innovation, extracurricular, cultural innovations, student personality traits, as well as academic and non-academic achievement development programs (School Engagement). The implementation of school quality development culture program encountered several obstacles including the lack of understanding of how to implement the 2013 curriculum. The application of the principles of transformational leadership and continuous mentoring to teachers in class assignments and responsibilities is a possible solution. The approach taken by the principal through the management approach is as follows: First, the planning phase which sets quality goals and communicates these goals to the school community. Second, the organizational stage by establishing an organizational structure, determining the main tasks and assigning or delegating tasks of authority. Third, the leadership phase consists of teacher training, assisting teachers and staff, observing teachers during learning, motivating, discussing results, focusing on quality goals, and following up. Fourth, the stage of monitoring and evaluating ongoing school programs. In addition, the results of this paper will describe the impact of transformational leadership on the development of innovation and work culture in leadership education. The writing of this article comes from scientific sources such as books and articles that have been checked for authenticity.